Synthesis of ZnO/SnO2 nanocomposite loaded with silver via liquid impregnation method and investigation of its photocatalytic activity in removing an environmental pollutant under visible light irradiation - Leila Airemlou (آلودگی‌های محیطی و توسعه پایدار شهری)
In this research, ZnO/SnO2 nanocomposite was first synthesized using the co-precipitation method, followed by the loading of silver at different percentages onto the nanocomposite via the liquid impregnation method. The photocatalytic activity of the synthesized materials in the removal of a dye pollutant (C.I. Acid Red 27) was evaluated under visible light. Material characterization was conducted using XRD and SEM-EDX methods. Through these analyses, the particle size, constituent phases, and morphology of the particles were determined. The photocatalytic activity results showed that the Ag-ZnO/SnO2 nanocomposite exhibited higher activity than the ZnO/SnO2 nanocomposite in pollutant removal. The highest photocatalytic activity was observed in the Ag-ZnO/SnO2 nanocomposite with 5% wt. silver and a calcination temperature of 500°C, achieving a 95% removal of Acid Red 27 after 50 min of irradiation.